Practical considerations for maximizing heat production in a novel thermobrachytherapy seed prototype. Issue 2 (8th January 2014) - Gautam, Bhoj; Warrell, Gregory; Shvydka, Diana; Subramanian, Manny; Ishmael Parsai, E.
Abstract : Purpose: : A combination of hyperthermia and radiation in the treatment of cancer has been proven to provide better tumor control than radiation administered as a monomodality, without an increase in complications or serious toxicities. Moreover, concurrent administration of hyperthermia and radiation displays synergistic enhancement, resulting in greater tumor cell killing than hyperthermia and radiation delivered separately. The authors have designed a new thermobrachytherapy (TB) seed, which serves as a source of both radiation and heat for concurrent brachytherapy and hyperthermia treatments when implanted in solid tumors. This innovative seed, similar in size and geometry to conventional seeds, will have self‐regulating thermal properties. Methods: : The new seedˈs geometry is based on the standard BEST Model 2301 125 I seed, resulting in very similar dosimetric properties. The TB seed generates heat when placed in an oscillating magnetic field via induction heating of a ferromagnetic Ni–Cu alloy core that replaces the tungsten radiographic marker of the standard Model 2301. The alloy composition is selected to undergo a Curie transition near 50 °C, drastically decreasing power production at higher temperatures and providing for temperature self‐regulation. Here, the authors present experimental studies of the magnetic properties of Ni–Cu alloy material, the visibility of TB seeds in radiographic imaging, and the ability of seed prototypes to uniformly heat tissue to a desirable temperature. Moreover, analyses are presented of magnetic shielding and thermal expansion of the TB seed, as well as matching of radiation dose to temperature distributions for a short interseed distance in a given treatment volume. Results: : Annealing the Ni–Cu alloy has a significant effect on its magnetization properties, increasing the sharpness of the Curie transition. The TB seed preserves the radiographic properties of the BEST 2301 seed in both plain x rays and CT images, and a preliminary experiment demonstrates thermal self‐regulation and adequate heating of a tissue‐mimicking phantom by seed prototypes. The effect of self‐shielding of the seed against the external magnetic field is small, and only minor thermal stress is induced in heating of the seeds from room temperature to well above the seed operating temperature. With proper selection of magnetic field parameters, the thermal dose distribution of an arrangement of TB and hyperthermia‐only seeds may be made to match with its radiation dose distribution. Conclusions: : The presented analyses address several practical considerations for manufacturing of the proposed TB seeds and identify critical issues for the prototype implementation. The authors' preliminary experiments demonstrate close agreement with the modeling results, confirming the feasibility of combining sources of heat and radiation into a single thermobrachytherapy seed.